2010
DOI: 10.1038/modpathol.2009.151
|View full text |Cite
|
Sign up to set email alerts
|

Collagenous sprue is not always associated with dismal outcomes: a clinicopathological study of 19 patients

Abstract: Collagenous sprue is associated with high morbidity; however, the etiology of this disorder is unclear. Data regarding the pathological and clinical manifestations of patients with collagenous sprue are also limited. We, thus, undertook this study to gain insight into the etiology, disease manifestations and outcomes of collagenous sprue. We searched our departmental database (1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008) to identify cases of collagenous sprue and to obtain clinical and laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
49
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(51 citation statements)
references
References 43 publications
2
49
0
Order By: Relevance
“…Indeed, there is recent evidence that these patients may be successfully treated (7), and the vast majority of patients with collagenous sprue (that sometimes display associated celiac disease) may have relatively good clinical outcomes (8).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is recent evidence that these patients may be successfully treated (7), and the vast majority of patients with collagenous sprue (that sometimes display associated celiac disease) may have relatively good clinical outcomes (8).…”
Section: Discussionmentioning
confidence: 99%
“…Histological alterations of intestinal villi may demonstrate subtotal or total atrophy. Patients die because of malnutrition, gastrointestinal system lymphomas, and infections [1,2,4]. Our patient died 5 months after being diagnosed because of an infection.…”
mentioning
confidence: 92%
“…However, collagenous sprue, refractory celiac disease, refractory sprue, and unclassified sprue may demonstrate similar features. Collagenous sprue is also considered a severe complication of celiac disease in some literature [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic inflammation could favor subepithelial accumulation of collagen and increase resistance to a GFD. In their series of 19 patients with collagenous sprue, Vakiani et al [18] observed that 17 had CD. Nine were primary or secondary resistant to a GFD at time of diagnosis of collagenous sprue, 8 with RCDI and 1 with RCDII.…”
Section: Complications and Outcomementioning
confidence: 99%